Simbolisme dalam Praktik Pengelolaan dan Komunikasi Keuangan di Kabupaten Luwu - Eva Astria; Antong Antong; Halim Usman (Universitas Muhammadiyah Purwokerto, 2026)
This study examines symbolism in the practice of village financial management and communication, as well as how these symbols are interpreted by village officials and the community in shaping transparency, accountability, and the legitimacy of village government. The study uses a qualitative approach with an interpretive paradigm based on symbolic interactionism theory. Data was collected through in-depth interviews, participatory observation, and document analysis of financial management in three villages in Luwu Regency and then analyzed interpretatively. The results show that accounting practices are interpreted in various ways, ranging from symbols of administrative order through reports and information boards, symbols of participation through deliberations, to symbols of morality and social trust through direct interaction between officials and villagers. Transparency in villages needs to consider the symbolic dimension and social communication in village accounting practices.